An empirical study exploring the relationship among human capital innovation, service innovation, competitive advantage and employee productivity in hospitality services - Vivek Sharma; Dada Ab Rouf Bhat (African Journal of Hospitality, Tourism and Leisure, 2020)
This study intends to examine whether hotels' human capital innovation initiatives are an important predictor of service innovation performance. For meeting the objectives of the study, the data was collected using a questionnaire from 245 staff members working in an A category hotel's in Jammu and Kashmir using a non probability convenience sampling technique. Structured equation modeling was used to test the hypothesis. Results revealed a positive impact of human capital innovation on service innovation. Further, the study found a significant impact of service innovation on employee performance and competitive advantage. The results enriched the knowledge regarding human capital innovation by revealing its influence on the hotel industry's service innovation performance in the form of competitive advantage. The study also leads to a number of future research directions for researchers as well as academicians.
Keywords: 330; Human capital innovation; Employee productivity; Service innovation; Competitive advantage